Empathic Concern and Internet Altruistic Behavior Among University Students in Riau: A Cross-Sectional Study - Itto Nesyia Nasution; Wita Indah Purnama; Ratna Sari (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
The increasing intensity of internet use has created new opportunities for voluntary helping behaviors through digital platforms, commonly referred to as Internet Altruistic Behavior (IAB). One psychological factor associated with such behavior is empathic concern, defined as feelings of sympathy and compassion toward individuals in need. This study aimed to examine the association between empathic concern and Internet Altruistic Behavior among university students. A quantitative cross-sectional design was employed involving 364 university students aged 18–25 years in Riau Province, selected using one-stage cluster probability sampling. Data were collected using an adapted Empathic Concern Scale and the Internet Altruistic Behavior Scale, both of which demonstrated satisfactory psychometric properties. Data were analyzed using simple linear regression. The findings showed that empathic concern was positively associated with Internet Altruistic Behavior (β = .649, p < .001, R² = .421). These findings indicate that university students with higher levels of empathic concern tend to report greater engagement in online prosocial behaviors. Because this study employed a cross-sectional design, causal inferences cannot be drawn. Additionally, the study assessed only the affective dimension of empathy rather than empathy as a multidimensional construct. The findings may inform the development of educational programs aimed at fostering empathic concern and promoting positive online social engagement among university students.